Fundamentos Técnicos do Tiro de Duelo - Alberto Gomes Santa Rosa; Robesio da Costa Vaz; David Rodrigues; Humberto de Azevedo Viana Filho; Victor Edgar Perez; Romualdo Varela (Brazilian Army, 2020)
Resumo do artigo "Fundamentos Técnicos do Tiro de Duelo"